KUALITAS TINGKAT PENGETAHUAN K3 (KESELAMATAN DAN KEAMANAN KERJA) MAHASISWA DI LABORATORIUM TERPADU KIMIA POLTEKKES KEMENKES GORONTALO - Agustian A Maridji; Fatmayanti Nawai; Denny Indra Setiawan; Misnati, Misnati; Mahyudin Bami; Nur Natalia H Uri (Journal of Innovation Research and Knowledge, 2024)
Background: Risk reduction due to work, occupational health and safety (OHS) practices must be implemented in the laboratory. The aim of this research is to assess the level of students' knowledge about occupational health and safety (OHS) in the integrated chemistry laboratory. Method: This research is a quantitative study conducted from July to August 2024 involving 182 students at the Poltekkes Kemenkes Gorontalo. Data collection was carried out by distributing pre and post questionnaires. Data analysis was processed using Excel and SPSS 16. Result: the quality of students' knowledge in occupational health and safety (K3) improved after receiving the material. The conclusion is that there has been an increase in knowledge from 59.07 in the poor category to 77.6 in the good category